Sosialisasi Cara Pembuangan Obat Rusak, Tidak Terpakai, dan Kedaluwarsa pada Masyarakat - Maifitrianti; Rusdi, Numlil Khaira; Nurhasnah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The community's habit of storing unnecessary, expired, and damaged medicines as well as the lack of knowledge about the correct way to dispose of medicines are problems that need to be followed up. One of the efforts to increase community knowledge is through education on how to properly dispose of medicines. Education through this service activity was carried out in the community in RT 004, RW 013 Pasir Angin Village, Cileungsi, West Java. Education was provided using the lecture method and leaflet media. The level of knowledge was assessed using a questionnaire before and after education. The service activities have been carried out well and the participants were enthusiastic during the activities. The results of the knowledge score analysis showed that there was a significant increase in knowledge before and after the activity (p<0.05).